KAJI BANDING STRATEGI PEMBELAJARAN MENYIMAK DAN BERBICARA DALAM BUKU TEKS BAHASA INDONESIA KURIKULUM MERDEKA - Ratna; Laili, Nur; Patmajaya, Dimas; Arianti, Martika; Karina Sari, Sindi; Fakihuddin, Lalu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze comparatively the listening and speaking learning strategies contained in the Indonesian language textbook Cerdas Cergas Berbahasa dan Bersastra Indonesia for Grade X Senior High School/Vocational High School based on the Merdeka Curriculum. This research employed a qualitative approach using descriptive content analysis. The data source was the Indonesian language textbook published by the Ministry of Education, Culture, Research, and Technology in 2021. Data were collected through documentation techniques by identifying, classifying, and analyzing learning activities related to listening and speaking skills. Data analysis was conducted through data reduction, data display, and conclusion drawing based on the aspects of learning objectives, learning activities, instructional strategies, and the characteristics of developed language competencies. The results show that listening learning strategies emphasize students’ abilities to identify, understand, analyze, and evaluate information critically through activities such as information verification, interpretation, and text analysis. Meanwhile, speaking learning strategies focus on students’ abilities to express ideas, present information, negotiate, and communicate through discussions, presentations, and creative performances. The comparison indicates that both strategies apply student-centered learning principles and support the development of critical thinking, communication, collaboration, and creativity. The novelty of this study lies in the comparative analysis of listening and speaking strategies within the Merdeka Curriculum textbook as an integrated framework for language competence development. The findings contribute to evaluating and improving Indonesian language textbooks to support effective and contextual language learning.